Measurement of differential cross sections for Σ+p elastic scattering in the momentum range 0.44–0.80 GeV/c. (4th September 2022) - Nanamura, T; Miwa, K; Ahn, J K; Akazawa, Y; Aramaki, T; Ashikaga, S; Callier, S; Chiga, N; Choi, S W; Ekawa, H; Evtoukhovitch, P; Fujioka, N; et al.
Abstract: We performed a novel Σ + p scattering experiment at the J-PARC Hadron Experimental Facility. Approximately 2400 Σ + p elastic scattering events were identified from 4.9 × 10 7 tagged Σ + particles in the Σ + momentum range 0.44–0.80 GeV/ c . The differential cross sections of the Σ + p elastic scattering were derived with much better precision than in previous experiments. The obtained differential cross sections were approximately 2 mb/sr or less, which were not as large as those predicted by the fss2 and FSS models based on the quark cluster model in the short-range region. By performing phase-shift analyses for the obtained differential cross sections, we experimentally derived the phase shifts of the 3 S 1 and 1 P 1 channels for the first time. The phase shift of the 3 S 1 channel, where a large repulsive core was predicted owing to the Pauli effect between quarks, was evaluated as 20^° |δ _^3S_1|35^° . If the sign of δ _^3S_1 is assumed to be negative, the interaction in this channel is moderately repulsive, as the Nijmegen extended-sort-core models predicted.